(untitled) (Ameghiniana, 2013)
Abstract. An example of application of calcareous microfossils to palaeoenvironmental reconstruction is presented. Foraminifers and Ostracoda from across the Aalenian-Bajocian boundary at the Picún Leufú section and Mid Callovian at the María Rosa Curicó section, both in Neuquén Basin, in central western Argentina, are analysed. The resulting data are presented as the following parameters: faunal density and specific diversity in both groups; test composition and vertical distribution of morphogroups in foraminifers; carapace morphology, adult valves to carapaces ratio and population age-structures in Ostracoda. Conclusions from the microfossils agree with those proposed by other authors based on sedimentological and palynological data. Additionally, two new Jurassic species (Middle Callovian) are described as new: the attached foraminifer Ammovertellina simeonae sp. nov. and the ostracod Cytherella mediodepressa sp. nov. Resumen. ESTUDIO MICROPALEONTOLÓGICO DE DOS SECUENCIAS DE LA CUENCA NEUQUINA, CENTRO OESTE DE ARGENTINA. Se analizan las asociaciones de foraminíferos y ostrácodos en las secciones Picún Leufú (límite Aaleniano-Bajociano) y María Rosa Curicó (Caloviano medio), ambas en la cuenca Neuquina. Los datos fueron organizados de acuerdo a los siguientes parámetros: densidad faunística y diversidad específica en ambos grupos; composición de la conchilla y distribución vertical de morfogrupos en foraminíferos; morfología del caparazón, relación en adultos entre valvas y caparazones y estructura poblacional en ostrácodos. Las conclusiones obtenidas a partir de los microfósiles coinciden con aquéllas provenientes de estudios sedimentológicos y palinológicos. Se describen como nuevos para el Caloviano medio, el foraminífero adherido Ammovertellina simeonae sp. nov. y el ostrácodo Cytherella mediodepressa sp. nov.